Calmodulin dissociation mediates desensitization of the cADPR-induced Ca2+ release mechanism. - Thomas, J; Summerhill, R; Fruen, B; Churchill, G; Galione, A (2002)
Ryanodine receptor (RyR) activation by cyclic ADP-ribose (cADPR) is followed by homologous desensitization. Though poorly understood, this "switching off" process has provided a key experimental tool for determining the pathway through which cADPR mediates Ca(2+) release. Moreover, desensitization is likely to play an important role in shaping the complexities of Ca(2+) signaling involving cADPR, for example, localized release events and propagated waves. Using the sea urchin egg, we unmask a role of calmodulin, a component of the RyR complex and a key cofactor for cADPR activity, during RyR/cADPR desensitization. Recovery from desensitization in calmodulin-depleted purified endoplasmic reticulum (microsomes) is severely impaired compared to that in crude egg homogenates. An active, soluble factor, identified as calmodulin, is required to restore the capacity of microsomes to recover from desensitization. Calmodulin mediates recovery in a manner that tightly parallels its time course of association with the RyR. Conversely, direct measurement of calmodulin binding to microsomes reveals a loss of specific binding during cADPR, but not IP(3), desensitization. Our results support a mechanism in which cycles of calmodulin dissociation and reassociation to an endoplasmic reticulum protein, most likely the RyR itself, mediate RyR/cADPR desensitization and resensitization, respectively.